2022
DOI: 10.3390/encyclopedia2030104
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Concept of Space up to Newton

Abstract: The concept of space, ubiquitous among all humans from birth, has changed profoundly in the course of the history of Western civilization, the only one to be considered here. An important contribution to this change was the theoretical elaborations of the philosophers of nature and mathematicians, started in Ancient Greece. Here, the process is considered up to Newton, when the concept of space for physicists, who then replaced the traditional philosophers of nature, took on a connotation that remained substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Throughout history, our notion of space and time has undergone dramatic transformations. Following the intuitive view of Euclid, Newton concluded that the external to the observer space is infinite, isotropic, uniform, perfectly penetrable, and immovable (i.e., absolute quantity), where he located the relative motion and studied its variation [42,43]. The Galilean principle of relativity formulated the first deviation from the intuitive interpretation of space and time.…”
Section: Space Time Symmetry and Relativitymentioning
confidence: 99%
“…Throughout history, our notion of space and time has undergone dramatic transformations. Following the intuitive view of Euclid, Newton concluded that the external to the observer space is infinite, isotropic, uniform, perfectly penetrable, and immovable (i.e., absolute quantity), where he located the relative motion and studied its variation [42,43]. The Galilean principle of relativity formulated the first deviation from the intuitive interpretation of space and time.…”
Section: Space Time Symmetry and Relativitymentioning
confidence: 99%
“…Following the intuitive view of Euclid and Galilei. Newton concluded that the external to the observer space is infinite, isotropic, uniform, perfectly penetrable, and immovable, where he located the relative motion and studied its variation [30,31]. The frequently discussed mystery of biological chirality [32] arose from the combination of intuitive illusions.…”
Section: Molecular Chiralitymentioning
confidence: 99%
“…where Γ is the integration constant having dimension [length 2 /time] and the denominator Σ(ν, t, σ) has a view…”
Section: The Quantum-mechanical Navier-stokes Equationmentioning
confidence: 99%
“…What is space, time, and matter motion? This question has accompanied humanity since antiquity [2]. The contrary views about space and time have developed in the form of two dialectical opposite ideas, later known as the Democritus-Newton and conceptions [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation